2008
DOI: 10.2460/ajvr.69.11.1496
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic effects of phenylbutazone on the right dorsal colon in horses

Abstract: Prolonged phenylbutazone administration caused hypoalbuminemia, neutropenia, changes in RDC arterial blood flow, and changes in VFA production. Veterinarians should monitor serum albumin concentrations and neutrophil counts and be cautious when making dosing recommendations for phenylbutazone treatment of horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 21 publications
4
46
0
5
Order By: Relevance
“…Colonic prostaglandins were assessed following phenylbutazone administration in horses and a difference was not observed (Meschter et al., ), but the study had the same sample size limitations as noted above for gastric prostaglandins. More recently, it was reported that phenylbutazone did not lower right dorsal colon PGE concentrations (McConnico, Morgan, Williams, Hubert, & Moore, ). In this study, horses included in analysis did develop hypoalbuminemia and neutropenia but not diarrhea.…”
Section: Introductionmentioning
confidence: 97%
“…Colonic prostaglandins were assessed following phenylbutazone administration in horses and a difference was not observed (Meschter et al., ), but the study had the same sample size limitations as noted above for gastric prostaglandins. More recently, it was reported that phenylbutazone did not lower right dorsal colon PGE concentrations (McConnico, Morgan, Williams, Hubert, & Moore, ). In this study, horses included in analysis did develop hypoalbuminemia and neutropenia but not diarrhea.…”
Section: Introductionmentioning
confidence: 97%
“…The case fatality rate may be as high as 50%. 336,587,588,589,626 Phenylbutazone causes changes in right dorsal colon arterial blood flow and changes in VFA production. 578,579 A 2014 study in Thoroughbred foals in central Kentucky found a mean prevalence of S. westeri infection of 30%, which was greater than previous reports from the area.…”
Section: Conditions Associated With Diarrheamentioning
confidence: 99%
“…The majority of infections with Strongyloides westeri are subclinical, but occasionally diarrhea can occur in foals with high worm burdens. 589 Diarrhea is a component of the clinical syndrome associated with several toxins. 579 Cryptosporidium spp.…”
Section: Conditions Associated With Diarrheamentioning
confidence: 99%
“…Gastrointestinal lesions caused by NSAIDs in dogs tend to be located in the pyloric antrum, and have a poor prognosis if not identified and treated early (Lascelles et al, 2005a). In horses, ulceration can occur anywhere along the gastrointestinal tract, including the colon; however, the right dorsal colon tends to be particularly sensitive to the toxic effects of NSAIDs (McConnico et al, 2008). Clinical signs of gastrointestinal erosions and ulcers include anorexia, depression, lethargy, diarrhea, vomiting, hematochezia, melena, abdominal pain, anemia, hypoproteinemia, leukocytosis or leukopenia, and increased blood urea nitrogen.…”
Section: Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…It is imperative that veterinarians educate their clients about proper dosing and use of phenylbutazone. Reports of toxicity in horses include gastric ulceration, renal papillary necrosis, vascular thrombosis, oral ulceration, negative effects on bone healing, and right dorsal colitis (Gunson & Soma, 1983;MacKay et al, 1983;MacAllister et al, 1993;Goodrich & Nixon, 2006;McConnico et al, 2008). More recently, the efficacy of suxibuzone, a prodrug of phenylbutazone, was evaluated (Sabate et al, 2009).…”
Section: Phenylbutazonementioning
confidence: 99%